2003
DOI: 10.1289/ehp.5907
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary exposure to some persistent organic pollutants in the Republic of Karakalpakstan of Uzbekistan.

Abstract: A 1999 study heightened long-standing concerns over persistent organic pollutant contamination in the Aral Sea area, detecting elevated levels in breast milk and cord blood of women in Karakalpakstan (western Uzbekistan). These findings prompted a collaborative research study aimed at linking such human findings with evidence of food chain contamination in the area. An international team carried out analyses of organochlorine and organophosphate pesticides, polychlorinated biphenyls (PCBs), polychlorinated dib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 24 publications
0
18
1
1
Order By: Relevance
“…The pesticide content reached 8% of the respective FAO/WHO limits (Arnold et al, 1998). However, it is important to note that some of the identified pesticides in this study, for example DDT and its metabolite DDE, together with β-HCH are known to suppress lactation (Muntean et al, 2003). These compounds are highly persistent and their continued presence at significant levels in the food supply is a matter of great health concern.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The pesticide content reached 8% of the respective FAO/WHO limits (Arnold et al, 1998). However, it is important to note that some of the identified pesticides in this study, for example DDT and its metabolite DDE, together with β-HCH are known to suppress lactation (Muntean et al, 2003). These compounds are highly persistent and their continued presence at significant levels in the food supply is a matter of great health concern.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have reported the presence of γ-HCH in plant, water, and sediment. Because of the high persistence and bioaccumulation of α-HCH and β-HCH, technical HCH mixtures were banned in almost all developed countries more than 25 years ago, but application of γ-HCH (lindane) is still allowed for specific purposes (Muntean et al, 2003). In Ghana, lindane has been in the provisional list of severely restricted pesticides since 1996 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Aral Sea area, agriculture mis-management (e.g. cotton monoculture, over irrigation, pesticide abuse) and accelerated desertification due to both environmental degradation and climate change, have resulted serious contamination of soil, water and local foods with high levels of POPs and dioxins, leading to critical health and socio-economic impacts to local populations (Muntean et al, 2003).…”
Section: Sea Level Risementioning
confidence: 99%
“…Individuals that have metabolic syndrome or that are obese usually have higher consumption of fatty foods from animal origin, which is associated with a greater body burden of lipophilic endocrine disruptors such as 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) (16,18,21,34). Elimination of TCDD is slowed substantially as body fat increases (10,32).…”
mentioning
confidence: 99%